Possibility of using retention reservoirs as flow controllers - Malmur, Robert; Pluta, Kamil; Świętochowski, Kamil; Kalenik, Marek (Instal, 2023)
Rainwater runoff from urban areas is mainly controlled by the use of storm sewage systems. These systems are expected to ensure efficient drainage of rainwater from urbanized areas in terms of quantity (prevention of flooding) and quality (reduction of pollutant load discharged to natural water reservoirs). It can be expected that standards for protecting surface water from rainwater runoff discharges will be tightened in the near future, and modernization of existing storm sewage systems will be necessary. Stormwater systems should be designed in a sustainable manner. However, they cannot be implemented everywhere, mainly due to dense urban development or unfavorable soil and water conditions. Therefore, the development and modernization of underground systems, mainly by increasing their retention capacity remain a important engineering problem. The present paper discusses the concept of using a retention reservoir as a controller of rainwater runoff distribution. It offers an alternative to the flow separators used in the storm sewage systems described in the literature.